Processing of the Passive Drilling-bit Ranging Signal Based on Wavelet Packet. Issue 1 (April 2021) - Yang, Quanzhi; Zhang, Xiaobin; Yu, Xiaolong; Yang, Xianlun; Li, Weifeng; Hou, Yunyi
Abstract: Recent technological advances have increased interest to acoustic ranging especially the passive acoustic ranging which is easier to operate in the oilfield. For analyzing the non-stationary drilling-bit signal, the conventional discrete Fourier Transform (DFT) has been known to be less efficient. A new extraction method based on wavelet packet (WP) is presented. In the signal processing, WP is used to decompose the original drilling-bit signal into the sub-frequency bands (SFBs). By analyzing energy spectrum of the SFBs, the first four SFBs are found that contain the characteristic of the drilling-bit, and the specific frequency band of the drilling-bit signal is determined after power spectrum analyzing. The field test shows that when the bit is near to the casing of the adjacent well, the reconstruction drilling-bit signal changes significantly which can give warning accurately.